Understanding the methodologies of the four sunni mazhabs - Zamri, Muhammad Zikril Hakimi; Ramlan, Muhammad Azzri Rifqi; Mohd Adanan, Muhammad Haris Iqbal; Tuan Zainal Abidin, Tuan Muhammad Lukman; Muhd Rafi, Muhammad Jamaluddin (2025)
Since the early development of Islamic civilization, Islamic jurisprudence (fiqh) has played a central role in guiding the lives of Muslims through various legal, ethical, and social matters. The evolution of fiqh is marked by the efforts of Muslim jurists who developed structured methodologies to derive rulings from Islam’s two primary sources: the Qur’an and the Sunnah. These methodologies laid the foundation for the formation of four major Sunni schools of law, known as the Hanafi, Maliki, Shafi’i, and Hanbali madhhabs. Each of these schools represents a unique intellectual framework that reflects the diverse approaches to interpreting and applying Islamic law. One of the defining characteristics of these madhhabs is their distinct legal methodologies, or usul al-fiqh, which govern how rulings are extracted. These methodologies involve principles such as qiyas (analogical reasoning), istihsan (juristic preference), maslahah (public interest), and other tools developed to ensure that Islamic law remains both authentic and applicable to new circumstances. For instance, while the Hanafi school places greater emphasis on rational analogy, the Maliki school values the practice of the people of Madinah. The Shafi’i school is known for its rigorous classification of sources, and the Hanbali school is closely text-based in its interpretations (Kamali, 2003). Central to the development and diversity of these legal schools are the concepts of ijtihad and taqlid. Ijtihad refers to the effort of a qualified scholar to independently derive rulings on issues not explicitly addressed in the revealed texts. During the formative period of Islamic law, ijtihad was the primary mechanism through which jurists addressed emerging societal issues. Conversely, taqlid, or adherence to established legal opinions, became prevalent as legal knowledge became more specialized and institutionalized. While some regard taqlid as a limitation to legal reform, others view it as a means of preserving the integrity and continuity of Islamic legal tradition (Rahimin Affandi Abdul Rahim, 2009). Studying the methodologies of the four Sunni madhhabs offers not only a window into the rich diversity of Islamic legal thought but also provides valuable insights into how the balance between tradition and innovation has been maintained. This knowledge is essential in understanding how Islamic law has remained relevant across centuries and continues to offer guidance in addressing contemporary challenges. Through comparative fiqh (fiqh muqaran), this study seeks to explore the foundational principles, interpretative strategies, and intellectual contributions of each madhhab in shaping the landscape of Islamic legal tradition.